Removal of Copper (II) and Zinc (II) ions from Aqueous Solution by Biosorption onto Aminated Tea Waste - Shrestha, Bindra; Homagai, P. L.; Pokhrel, M. R.; Ghimire, K. N. (Journal of Nepal Chemical Society, 2013)
An efficient and cost effective non-conventional biosorbent has been prepared from tea waste by amination with ethylenediamine. The prepared adsorbent, ATW was characterized using elemental analysis, scanning electron microscopic image and FTIR spectroscopy. Its adsorption behavior for Cu++ and Zn++ ions was studied by using batch adsorption method. The maximum adsorption capacity onto ATW was found to be 46.4mg/g and 30.08 mg/g for Cu++ and Zn++ respectively. The effect of pH of solution, initial metal concentration and contact time for removal of metal ions were studied. The applicability of data was analyzed by Langmuir isotherm. The kinetics of removal of Cu++ and Zn++ ions was studied using pseudosecond order model, in which the data were well fitted. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8058 Journal of Nepal Chemical Society Vol.28, 2011 Page 48-53 Uploaded date: May 7, 2013